ANALISIS PENGUJIAN PROTEKSI SALURAN TRANSMISI MENGGUNAKAN DISTANCE RELAY PADA BAY LINE SENGKOL–KUTA DI GI 150 KV SENGKOL - Adi, Haris Setyo; Muljono, Agung Budi (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Distance relay is a crucial component in the protection system of high-voltage transmission lines. Faults on transmission lines can cause equipment damage and disrupt the continuity of power supply. This study aims to evaluate the performance and characteristics of the distance relay on the Sengkol–Kuta transmission line bay at the 150 kV Sengkol Substation. The testing method employed is shutdown testing, referring to IEC 60255-121:2014 and SPLN No.15 of 2014 standards. The test was conducted using an Omicron CMC 356 test set and Test Universe software. The protection zones examined include zone-1 and zone-2, with impedance and operating time parameters adjusted according to the line length. The results indicate that the MiCOM P543 relay operates accurately and responsively to simulated faults, as demonstrated by Mho and Quadrilateral characteristic curves that align with the protection system boundaries. These findings confirm that the implemented distance relay protection system functions optimally in fault detection and contributes to maintaining the reliability of the power system.